The effects of nanoclay and tin(IV) oxide nanopowder on morphological, thermo-mechanical properties of hexamethylene diisocyanate treated jute/bamboo/polyethylene hybrid composites - Fui, Kiew Liew; Sinin, Hamdan; Md Rezaur, Rahman; Mohamad Rusop, Mahmood; Chang, Josephine Hui Lai (Society of Plastics Engineers (SPE) t, 2017)
Hybrid composites were fabricated by hexamethylene diisocyanate (HDI) treated jute–bamboo fiber, nanoclay, tin(IV) oxide nanopowder, and low-density polyethylene. The composites were characterized by Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis, and differential scanning calorimetry. Surface morphology, tensile testing, and water absorption test were also reported. FTIR results revealed that treated fiber had covalence bonding with polymer matrix which enhanced mechanical properties. All HDI-treated hybrid composites showed significant improvement in activation energy, lower crystallinity index, significant high tensile strength, and Young's modulus compared to untreated hybrid composites. All treated hybrid composites also showed extreme low water absorption. The addition of nanoclay or tin(IV) oxide into treated hybrid composites had a negative impact on thermal-mechanical properties. Surface morphological results revealed the bonding condition among hybrid composites.